Koncept śmierć w poezji emigracyjnej Nadieżdy Teffi - NDiaye, Iwona Anna (Acta Polono-Ruthenica, 2018)
Nadezhda Teffi (former Buczynska, born as Lochwicka, 1872-1952) - poet and novelist, one of the most interesting characters in Russian literature of the first half of the twentieth century. In 1920 Teffi left Russia supplying the same community of thousands of Russian immigrants. In Paris, still accompanied by the opinion of eminent satirist, but a poetic works can trace many aspects of the Teffi creative attitude, and especially reflective and nostalgic nature of the emigration work. The experience of exile provoked to think about the country, the world and herself in this world. Similar sentiments reflect the poems included in the books of poetry: Шамрам. Песни Востока (Songs of the East, Berlin, 1923), Passiflora (Berlin 1923) and in the poems published in collective volumes and anthologies. The article analyses the concept of death in the lyrics of Teffi. Semantical structure of this concept includes both objective senses and individual imaginations of the author.